1979
DOI: 10.1148/132.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Platelet Aggregation by Contrast Media

Abstract: The effect of 30% Urografin on platelet aggregation induced by adenosine diphosphate (ADP), epinephrine, and arachidonic acid was examined. In vivo and in vitro experiments in 10 nondiabetic subjects and in vitro experiments in 7 diabetic-uremic patients showed a statistically significant decrease in platelet aggregation 20 minutes after in vitro incubation or in vivo infusion with Urografin. Urografin concentration was about 2.4-2.5%. The possibility of bleeding induced by contrast media and the connection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This general observation parallels several previously published reports suggesting inhibition of platelet aggregation by various RCM [3,4,[6][7][8]111. An inhibitory effect of similar magnitude was noted for RCM concentrations of 1, 2.5, 5 and 7.5 percent by volume.…”
Section: Aggregation Kineticssupporting
confidence: 91%
See 1 more Smart Citation
“…This general observation parallels several previously published reports suggesting inhibition of platelet aggregation by various RCM [3,4,[6][7][8]111. An inhibitory effect of similar magnitude was noted for RCM concentrations of 1, 2.5, 5 and 7.5 percent by volume.…”
Section: Aggregation Kineticssupporting
confidence: 91%
“…Subsequent studies [5,6] have suggested inhibition of aggregation appearing within 1 1/2 to 3 min. of RCM exposure, but whether the ex vivo effect is persistent [3,4] or more transient (returning to normal within 15 min [6], is controversial. We did not study aggregation kinetics for platelet-RCM exposure times exceeding 20 min.…”
Section: Time Course Of Effectsmentioning
confidence: 99%
“…It is interesting to note that the only previous study to suggest that non-ionic contrast media cause platelet aggregation used heparin as an anticoagulant, which, like hirudin, maintains plasma divalent cation concentrations at a physiological level (Hay & Bull, 1995). Other studies in which citrate was used as anticoagulant suggest that contrast media inhibit platelet aggregation (Gafter et al, 1979;Dawson et al, 1986;Taylor et al, 1991;Carr et al, 1995;Tamura et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that non-ionic low-osmolar contrast media can cause degranulation (Chronos et al, 1993;Hardeman et al, 1994;Van Beek et al, 1994;Albanese et al, 1995;Koza et al, 1995;Grabowski et al, 1995;Corot et al, 1996;Hay & Bull, 1995), which, through release of aggregating agents stored in intracellular granules, would be expected to be associated with platelet aggregation. However, the situation is confused by other reports that suggest that some contrast media inhibit platelet aggregation (Gafter et al, 1979;Dawson et al, 1986;Taylor et al, 1991;Carr et al, 1995;Tamura et al, 1995). In only one in vitro study has there been any indication that platelet aggregation can occur as a direct consequence of adding a contrast agent to blood (Hay & Bull, 1995).…”
mentioning
confidence: 98%
“…Diatrizoate contrast media have been found to inhibit human platelet aggregation after incubation with platelet-rich plasma (Gafter et al, 1979;Goldstone, 1974;Shapiro et al, 1977;Zir et al, 1974) and after in vivo use (Gafter et al, 1979;Shapiro et al, 1977;Zir et al, 1974). Shapiro et al (1977) found a prolonged template bleeding time in 3 of 13 patients after cardiac angiography with 210-560 ml of Renografin 76.…”
Section: Introductionmentioning
confidence: 99%